Developing Problem-Based Learning Student Worksheets to Enhance Higher-Order Thinking Skills in Elementary Science Education - Novita Sari; Zelhendri Zen; Zuwirna; Rayendra (Jurnal Penelitian Pendidikan IPA, 2025)
The need to strengthen students’ analytical, evaluative, and creative thinking in Science Education has prompted the development of instructional tools that go beyond rote memorization. This research aims to develop Student Worksheets using a Problem-Based Learning approach to improve Higher-Order Thinking Skills among fifth-grade elementary students. The study employed a research and development method adapted from the Plomp model, consisting of preliminary research, prototyping, and assessment phases. Data were collected through expert validation, teacher and student response questionnaires, and learning outcome tests involving 30 students in one elementary school. The developed worksheet demonstrated very high validity in content, design, and language. Practicality scores from individual, small group, and classroom trials showed consistent results in the “very practical” category. Effectiveness was confirmed through a notable increase in student scores from pre-test to post-test, reaching a class mastery level of 80 percent. The findings suggest that the worksheet successfully fosters student engagement in scientific inquiry while enhancing cognitive skills. This product offers a practical and pedagogically sound tool to support active learning in elementary Science Education and contributes to the broader development of inquiry-based learning strategies in the classroom.